Los abismos (2021) de Pilar Quintana: una actualización de Madame Bovary a partir del deseo triangular de René Girard - Álvarez Torres, Jonathan Paúl (2023)
On this essay we pretend to show that the novel Los abismos (2021) by Pilar Quintana is an actualization of Flaubert’s Madame Bovary (1856). This novel is going to be read through the triangular desire, Girard´s proposal on Mentira romántica y verdad novelesca (1985). The philosofical postulates used are, mainly, the girardians. Nevertheless, we used too, subsidiarily, postulated by Walter Benjamin.